DUKUNGAN KELUARGA BERHUBUNGAN DENGAN KEPATUHAN DIET HIPERTENSI PADA LANSIA - Riyadi, Muskhab Eko; Anggraeni, Riska Aprilia (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
Family support is the most important factor in helping elderly people to solve their health problems, one of which is because the family's role is very crucial in preventing an increase in blood pressure in the elderly. There are several forms of family support that can be provided to elderly hypertension sufferers, such as fulfilling dietary compliance and motivating them in treating hypertension. The aim of the research was to determine the relationship between family support and hypertension diet compliance among the elderly at the Elderly Posyandu in Kretek Bantul. This is a quantitative study with a cross-sectional design. The population in this study was 40 elderly people with a history of hypertension who were undergoing the Elderly Posyandu program at Donotirto Kretek Bantul. Based on calculations, the minimum sample size was 30 respondents. The sampling technique uses the convenience sampling technique. The instruments in this study were a questionnaire adopted from Chasanah (2022) to measure family support and the Dietary Salt Reduction Self-Care Behavior Scale (DSR-SCB scale) to determine the diet compliance of elderly hypertension. Statistical tests use the Kendall-Tau test. The results of the research showed that the majority of elderly people at Elderly Posyandu in Kretek Bantul had family support in the sufficient category, namely 15 respondents (50%), and had diet compliance in the obedient category, namely 18 respondents (60%). Statistical tests show a p-value of 0.002 and a correlation coefficient of 0.554. The conclusion is that there is a moderate relationship between family support and hypertension diet compliance in the elderly at the Elderly Posyandu in Kretek Bantul, and it is recommended for the elderly to increase the level of diet compliance so that the serious risk of hypertension can be avoided.